Efektivitas Asas Audi et Alteram Partem dalam Menjamin Keadilan Prosedural pada Sistem Penyelesaian Sengketa Litigasi dan Non-Litigasi - Kevin Daffa Arbi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study examines the effectiveness of the audi et alteram partem principle in ensuring procedural justice within litigation and non-litigation dispute resolution systems in Indonesia. This principle affirms the right of every party to be heard equally before a decision is rendered, as part of the due process of law and procedural justice. This research is a normative legal study employing statutory and conceptual approaches. The findings indicate that in litigation mechanisms, the audi et alteram partem principle has strong normative guarantees through procedural law, rendering it relatively effective in providing procedural protection. However, in practice, obstacles remain, such as limited access to legal aid and the lengthy judicial process. Meanwhile, in non-litigation mechanisms, this principle is applied more flexibly, but its effectiveness is highly dependent on the balance between the parties and the role of the mediator or arbitrator. Thus, the effectiveness of this principle is contextual and not absolute, but rather influenced by the characteristics of each dispute resolution mechanism.